Actitud del personal de salud responsable de la vigilancia epidemiológica - Vásquez-Chacón, Mariclaudia Leandro; Díaz-Vélez, Cristian; Sisniegas-Vergara, César; Seclén-Ubillús, Yovanna M. (Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo, 2020)
Carta al editor (sin resumen)